Depression in the Family of Patients With Dementia in Korea. (September 2016) - Jang, Sung-In; Bae, Hong-Chul; Shin, Jaeyong; Jang, Suk-yong; Hong, Seri; Han, Kyu-Tae; Park, Eun-Cheol
Introduction: Dementia is the leading cause of disability worldwide in the elderly individuals. Although prior studies have examined psychiatric symptoms in dementia caregivers, few studies have examined physician-diagnosed depression in the family caregiver of a patient with dementia. Methods: We used data from 457 864 respondents from the Korea Community Health Survey. We used logistic regression to examine the relationship between physician-diagnosed depression and cohabitation with a patient with dementia. Results: Cohabitation with a patient with dementia (1.2% of the Korean population) was significantly associated with physician-diagnosed depression. The significance remained in females when the data were stratified by sex. A significant association also occurred among males with low family income. Conclusion: To reduce the burden of dementia, we need a management policy that includes the caregiver as well as the patient with dementia. In particular, political management for the vulnerable population, male caregiver in low-income family and female caregiver in high-income family, should be prepared.